Practices of Ritualization in a Dutch Hospice Setting - Weegen, Kim van der (Religions, 2020)
In this article, we explore rituals and ritualized care practices in a hospice in the Netherlands. The research is guided by two research questions. First, we want to know what kind of rituals and ritualized care practices are taking place in the hospice. Second, we aim to understand these practices from a cultural perspective, i.e., to what cultural values do these practices refer? We distinguish five types of ritual: (1) care practices in the morning; (2) meals; (3) care practices in the evening; (4) care practices in the dying phase; (5) a farewell ritual after a patient has died. Ritualization takes place in various degrees and forms, depending on changes in the state of liminality. Analysis of ritualized care practices shows that everyday care practices are enriched with non-instrumental elements that have a strong symbolic meaning, referring to the cultural value of the ‘good death’.